Role of Coordination Environment in Synergistic Catalysis: A Molecular Orbital Perspective on M1M2N6 Catalysts - Zhangsheng Shi; Ziyang Wu; Zheng Shu; Xin Wang (Journal of the American Chemical Society, 2026)
Abstract Visualizing the coordination environment-dependent synergistic mechanisms that govern the structural stability and adsorption behavior of dual-atom catalysts (DACs) is pivotal for precise catalyst design. However, insights into these mechanisms at the molecular orbital level remain elusive. Herein, we present large-scale density functional theory calculations to elucidate how synergistic effects arise from the combination of d atomic orbitals into molecular orbitals between M1 and M2 sites, with notable variations observed from M1–N3–M2–N3–C to M1–N4–M2–N4–C. We identify an average weakening of M1/M2–N bond strength in M1–N3–M2–N3–C relative to M1–N4–M2–N4–C, which is attributed to a shift from direct dx2–y2 orbital overlap to nitrogen-mediated interactions involving the hybridization of bridge nitrogen 2p orbitals. Using hydrogen as a model adsorbate, we demonstrate that hydrogen adsorption on M1–N3–M2–N3–C shifts from wild modulation via a bridge configuration to mild modulation through an end-on configuration, signifying a selective orbital coupling from dx2–y2 to dz2 orbitals. In contrast, hydrogen adsorption on M1–N4–M2–N4–C exhibits only mild modulation via an end-on configuration. This behavior is ascribed to the symmetry constraints of antibonding (d-d/d*)-p* molecular orbitals near the Fermi level, mediated by nitrogen-mediated dz2-dz2* molecular orbitals. Furthermore, machine learning analyses corroborate these coordination environment-dependent synergistic mechanisms. Our findings provide a comprehensive molecular orbital-level understanding of how the interplay between coordination environments and electronic structures influences the properties of M1M2N6 catalysts, thereby establishing a theoretical framework for enhanced DACs design.